Hydrolysis rate constants and activation parameters for phosphate- and phosphonate-bridged phthalonitrile monomers under acid, neutral and alkali conditions - Kirill S. Belsky; Artem V. Sulimov; Boris A. Bulgakov; Alexandr V. Babkin; Alexey V. Kepman (Data in Brief, 2017)
Hydrolysis data for Bis(3-(3,4-dicyanophenoxy)phenyl) phenyl phosphate and Bis(3-(3,4-dicyanophenoxy)phenyl) phenylphosphonate under pH 4, 7 and 10 are presented. Conversion/time plots collected by HPLC analysis, typical chromatograms and NMR spectra of the reactions products are given. Pseudo-first order rate constants are determined for both substrates at 25, 50 and 80 °C. Activation parameters were calculated from Arrhenius equation. Keywords: Hydrolysis, Phthalonitrile, Phosphoric ester, Phosphonic ester, Rate constant, Activation energy